Acute Kidney Injury in the Intensive Care Unit According to the RIFLE - Azime BULUT; Oktay DEMİRKIRAN (Forbes Tıp Dergisi, 2023)
Objective: The RIFLE classification is widely used to decide when to start renal replacement therapy (RRT) in patients with acute kidney injury (AKI). In this study, we aimed to examine the frequency, etiology, and effects of mortality and morbidity of AKI in intensive care unit (ICU), and whether the timing of continuous RRT is associated with survival using the RIFLE classification. Methods: Two hundred-ninety one patients hospitalized in the ICU between 2012 and 2013 were retrospectively analyzed after the approval of the ethics committee. Patients with previous kidney failure or kidney transplantation, those under the age of 18, and those who were hospitalized in the ICU for 24 h were excluded from the study. The clinical, laboratory, and demographic data of the patients and their survival were evaluated. Results: AKI was detected in 27% (n=67) of 244 patients, according to the RIFLE classification, within the first 24 h of admission to the ICU. While 47.7% (n=32) of 67 patients were followed up with sepsis and 52.2% (n=35) had non-sepsis causes. While patients with AKI had 64.1% mortality, the mortality of patients without AKI was 25.9%. There was also a significant difference in mortality between the RIFLE stages. It was correlated with the Acute Physiological and Chronic Health Evaluation-II score. Conclusion: RIFLE classification can predict hospital mortality and short-term prognosis in patients with sepsis in the ICU.